Confiding through Artificial Intelligence: Can ChatGPT Provide Emotional Support? - Moch. Arifudin; Inayatur Robbaniyah; Idang Ramadhan (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2024)
In the increasingly developing digital era, human interaction with artificial intelligence (AI) such as ChatGPT is becoming an increasingly common phenomenon. ChatGPT is used for various purposes, including sharing personal stories or venting. This study seeks to understand whether ChatGPT can provide emotional support to its users, and how it is perceived by users. This discussion explores three main aspects: encouragement and enthusiasm, acceptance and validation, and appreciation and empathy. This study uses a qualitative research method involving seven people who have interacted and used ChatGPT as a place to vent. This study shows that ChatGPT has the potential to be a complementary tool in providing emotional support in the form of validation, appreciation, and practical encouragement. However, due to its limitations as an AI, in-depth and authentic support still requires human interaction. Therefore, ChatGPT is more suitable for practical needs or urgent situations, while complex emotional support is best provided by professionals or social networks.